Closing the case of APOE in multiple sclerosis: no association with disease risk in over 29 000 subjects. Issue 9 (11th September 2012) - Lill, Christina M; Liu, Tian; Schjeide, Brit-Maren M; Roehr, Johannes T; Akkad, Denis A; Damotte, Vincent; Alcina, Antonio; Ortiz, Miguel A; Arroyo, Rafa; Lopez de Lapuente, Aitzkoa; Blaschke, Paul; Winkelmann, Alexander; et al.
Abstract : Background: Single nucleotide polymorphisms (SNPs) rs429358 (ε4) and rs7412 (ε2), both invoking changes in the amino-acid sequence of the apolipoprotein E ( APOE ) gene, have previously been tested for association with multiple sclerosis (MS) risk. However, none of these studies was sufficiently powered to detect modest effect sizes at acceptable type-I error rates. As both SNPs are only imperfectly captured on commonly used microarray genotyping platforms, their evaluation in the context of genome-wide association studies has been hindered until recently. Methods: We genotyped 12 740 subjects hitherto not studied for their APOE status, imputed raw genotype data from 8739 subjects from five independent genome-wide association studies datasets using the most recent high-resolution reference panels, and extracted genotype data for 8265 subjects from previous candidate gene assessments. Results: Despite sufficient power to detect associations at genome-wide significance thresholds across a range of ORs, our analyses did not support a role of rs429358 or rs7412 on MS susceptibility. This included meta-analyses of the combined data across 13 913 MS cases and 15 831 controls (OR=0.95, p=0.259, and OR 1.07, p=0.0569, for rs429358 and rs7412, respectively). Conclusion: Given the large sample size of our analyses, it is unlikely that the two APOE missense SNPs studied here exert any relevant effects on MS susceptibility.